Tindakan Pencegahan Plebitis Terhadap Pasien Yang Terpasang Infus di RSU Mokopido Tolitoli - Fitria, Fitria; Effendy, Christantie; Pangastuti, Heny Suseani (School of Nursing Faculty of Medicine Universitas Gadjah Mada, 2008)
Please refer to the file